Mitochondrial lipid peroxidation is necessary but not sufficient for induction of ferroptosis - Huan, He; Lyamzaev, Konstantin G.; Panteleeva, Alisa A.; Chernyak, Boris V. (Frontiers in Cell and Developmental Biology, 2024)
Ferroptosis, a form of regulated cell death mediated by lipid peroxidation (LPO), has become the subject of intense research due to its potential therapeutic applications in cancer chemotherapy as well as its pathophysiological role in ischemic organ injury. The role of mitochondrial lipid peroxidation (LPO) in ferroptosis remains poorly understood. We show that supplementation of exogenous iron in the form of ferric ammonium citrate (FAC) in combination with buthionine sulfoximine (BSO, an inhibitor of glutathione biosynthesis) induces mitochondrial lipid peroxidation that precedes ferroptosis in normal human fibroblasts. The mitochondrial-targeted antioxidant SkQ1 and the redox mediator methylene blue, which inhibits the production of reactive oxygen species (ROS) in complex I of the mitochondrial electron transport chain, prevent both mitochondrial lipid peroxidation and ferroptosis, but do not affect the cytosolic ROS accumulation. These data indicate that mitochondrial lipid peroxidation is required for ferroptosis induced by exogenous iron. FAC in the absence of BSO stimulates mitochondrial peroxidation without reducing cell viability. Glutathione depletion by BSO does not affect FAC-induced mitochondrial LPO but strongly stimulates the accumulation of ROS in the cytosol. These data allow us to conclude that mitochondrial LPO is not sufficient for ferroptosis and that cytosolic ROS mediates additional oxidative events that stimulate ferroptosis in conjunction with mitochondrial LPO.